Virulence and Antifungal Susceptibility of Microsporum canis Strains from Animals and Humans - Aneke, Chioma Inyang; Rhimi, Wafa; Hubka, Vit; Otranto, Domenico; Cafarchia, Claudia (Antibiotics (Basel, Switzerland), 2021)
The enzymatic and antifungal profiles of dermatophytes play an important role in causing infections in humans and animals. This study aimed to assess the virulence factors produced by Microsporum canis strains, in vitro antifungal profile and the relationship between virulence, antifungal profile and occurrence of lesions in animals and humans. A total of 100 M. canis strains from humans with tinea corporis (n = 10) and from animals presenting (n = 64) or not (n = 26) skin lesions was employed to evaluate phospholipase (Pz), hemolytic (Hz), lipase (Lz), catalase (Ca), and thermotolerance (GI) activities. In addition, in vitro antifungal profile was conducted using the CLSI broth microdilution method. A statistically significant difference (p < 0.05) in Lz and Ca values was revealed among strains from hosts with and without lesions. Voriconazole, terbinafine, and posaconazole were the most active drugs followed by ketoconazole, griseofulvin, itraconazole, and fluconazole in decreasing activity order. The significant positive correlation between azole susceptibility profile of M. canis and virulence factors (i.e., hemolysin and catalase) suggest that both enzyme patterns and antifungal susceptibility play a role in the appearance of skin lesions in animals and humans.
Keywords: dermatophytes; Microsporum canis; antifungal susceptibility testing; catalase; thermotolerance; phospholipase; virulence enzymes